Attentional Process During Listening to Quantitative Quranic Verses (Fatihah Chapter) Associated with Memory, Speech and Emotion - Rohayah, Husain; Hafizan, Juahir; Samhani, Ismail (2018)
Attentional problem associated with negative emotions can prolong irritable episodes, and apparently related to inhibitory incapability and memorial dysfunction. Quantitative Verse, the first chapter with rhymed proses and beauty literary rhythms, found to be endowed with cognitive and psychoacoustical effects that eliminate negative emotions and improving emotional and speech fluency. Twenty-eight normal subjects’ brainwaves were analyzed after given auditory stimulation of Quantitative Verse recited by Abdul Basit Abdul Samad. The alpha waveforms were analyzed by Fast Fourier Analysis (FFT) to get the power in frequency bands. Results were further analyzed by the Brain Electrical Stimulation Analysis (Besa 6.1) and XLSTAT for statistical analysis. Results showed areas modulate emotion and speech were strikingly significant decreased with p<0.05. The right inferior frontal (F8) and middle temporal (T8) were significantly decreased their synchronization reflecting increase in inhibition of distractors may well give effects to focus to the goal; and in short term memory that pulling the positive thoughts whilst expelling negative rumination can increase short term memory. While the significant result in the left inferior frontal (F7) and middle temporal (T7) showed improvement in speech fluency and memory. Listening to Arabic news increased speech fluency as well.